Melampaui Kepentingan Nasional: Kerjasama Mutual Legal Assistance (MLA) antara Swiss dan Indonesia dalam Menangani Kejahatan Pencucian Uang - Suci Permata Zetri; Mohamad Rosyidin; Muhammad Faizal Alfian (Journal of International Relations, 2022)
Money laundering is the act of disguising the origin of money resulting from a crime so that it appears as if it came from a legal act. Money laundering is a transnational crime because its actions and impacts reach across countries. Therefore, international cooperation is needed in dealing with money laundering. Indonesia decided to propose Mutual Legal Assistance (MLA) with Switzerland to investigate money laundering cases that had been committed by Indonesian citizens in Switzerland. After several negotiations, Switzerland finally agreed to cooperate with Indonesia in bilateral cooperation on Mutual Legal Assistance (MLA). Before this collaboration was agreed, Switzerland was known for its very strict banking secrecy system. From this phenomenon of Indonesia-Switzerland bilateral cooperation, a question arises as to why Switzerland which is known for its bank secrecy, is willing to assist Indonesia in tracing the money laundering case. To answer this question, the authors use a norm-based constructivist theory in conducting this research. The main argument of this study is that Switzerland's decision to agree to bilateral Mutual Legal Assistance (MLA) cooperation with Indonesia was driven by compliance with international norms formed from international regimes agreed upon by Switzerland. The type of data used in this study is qualitative and analyzed using congruent analysis methods.